2016
DOI: 10.15407/spqeo19.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical parameters of Cu6PS5I-based thin films deposited using magnetron sputtering

Abstract: Abstract. Cu 6 PS 5 I-based thin films were deposited onto silicate glass substrates by nonreactive radio-frequency magnetron sputtering. The chemical composition of thin films was determined using energy-dispersive X-ray spectroscopy. Electrical conductivity of Cu 6 PS 5 I-based thin films was studied as dependent on chemical composition. Optical transmission spectra of Cu 5.46 P 1.68 S 5.06 I 0.80 thin film were investigated within the temperature interval 77…300 K; temperature behaviour of optical absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…In Ref. [8], it was shown that the optical absorption edge for non-irradiated Cu 6 PS 5 Ibased thin films in the region of its exponential behaviour is described by the Urbach rule [10] ( )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [8], it was shown that the optical absorption edge for non-irradiated Cu 6 PS 5 Ibased thin films in the region of its exponential behaviour is described by the Urbach rule [10] ( )…”
Section: Methodsmentioning
confidence: 99%
“…Electrical studies have shown that the total electric conductivity of the Cu 6 PS 5 I-based thin films increases with increase of Cu atoms content [8]. Thus, with the Cu content increase in the interval from Cu 5.37 P 1.88 S 5.04 I 0.71 to Cu 7.55 P 0.89 S 3.44 I 1.12 , the electric conductivity increases from 0.044 to 0.066 S/m.…”
Section: Introductionmentioning
confidence: 99%
“…Cu content increase caused rapid decrease of the films hardness to around 0.7 GPa. At the same time, the conductivity of these films increased [24,25]. It is well known that high ionic conductivity of the investigated thin films is caused by formation of conductive channels from dendrites and crystal clusters by spinodal decomposition when the copper content increases [26].…”
Section: Nanoindentation In Thin Filmsmentioning
confidence: 73%
“…Electrical and optical studies of Cu 6 PS 5 I-based thin films with a different copper atoms content were performed in Ref. [9].…”
Section: Introductionmentioning
confidence: 99%